Metrópole institucional e vivida em Palmas - TO (2012-2018) - Soares, Dalva Marçal Mesquita (2019)
The process of institutionalization and or creation of the Metropolitan Regions in Brazil presents itself in two periods. The first begins with the Federal Constitution of 1967, whose prerogative rested with the Union, by means of Complementary Law. The second period begins after the promulgation of the Federal Constitution of 1988, when the Government transposed to each federated State, starting from Art. 25, § 3, the competence to establish the Metropolitan Regions (RMs), as well as to establish its own criteria of institution. This opening triggered the institutionalization of a large number of regional units, often without the minimum predicatives of a metropolitan region, given the establishment of inadequate criteria and the lack of parameters / instruments for analyzing the existence of the metropolitan fact. The RMs instituted until 2015 were based only on this article, since the government only established general guidelines for the planning, management and execution of public functions of common interest in metropolitan regions and in urban agglomerations instituted by the Publication of the Statute of the Metropolis (EM) (Law no. 13.089 / 2015). Thus, it occurred with the Metropolitan Region of Palmas (RMP), established by means of the Complementary Law of n. 90, December 2013, because the minimum predicatives were not considered, as the MS was only edited after the establishment of the RMP. This study aimed to analyze the process of institutionalization of the RMP, its true metropolitan character and its existence. As a methodological parameter for analysis of metropolitan facts, it was proposed to define criteria already used by other regions; defined by other authors; the prerogatives of the EM / 2015 and the changes suffered by it through Law no. 13,683, June 2018; and the studies on Regions of Influences of Cities - REGIC, carried out by the Brazilian Institute of Geography and Statistics - IBGE (2008). This is a qualitative and quantitative research, whose methodological procedures used for data collection varied according to the circumstances or type of investigation. In general terms, the following research instruments were used: bibliographic sources, documentary collection, interviews (open and closed), questionnaire and content analysis. As a main result, it was identified that the RMP was institutionalized based on political criteria and was not implemented, even though the RMP was legally instituted, as it is supported by the Federal Constitution. Finally, when analyzing the technical- socioeconomic, morphological, demographic and structural / functional factors, according to the criteria and parameters stipulated for analysis, the RMP has no metropolitan character. However, when analyzing the legal factor, through the interpretation of the concepts, established after review of the EM, in 2018 and the classification of Regions of Influence of Cities - REGIC performed by IBGE (2008), one identifies the existence of a metropolis and metropolitan region in Palmas.